Small Cell Neuroendocrine Tumour of Bladder: A Rare Entity and Review of the Literature - Muhamad Hud Muhamad Zin; Mohd Firdaus Mohd Hayati; Mohamed IzzadIshak; Siti Atiqah Abdul Halim; Isa Mohamed Rose; Fam, Xeng Inn; Zulkifli Md Zainuddin (Gazi Universitesi, 2022)
Small cell neuroendocrine cancer of the bladder (SCNCB) is a rare tumor with highly aggressive characteristics and poor differentiation. It comprises less than 1% of bladder malignancy and usually diagnosed at an advanced stage. It is challenging to differentiate between SCNCB with other bladder tumors as they had a similar presentation. We presented a case of a 60-year-old gentleman who presented with painless hematuria and ultrasound and cystoscopy examination show mass on the right urinary bladder wall. Computed tomography revealed urinary bladder mass with invasion to the prostate. Histopathological examination after transurethral resection of bladder tumor display features consistent with small cell neuroendocrine carcinoma with muscularis propria invasion, positive for synaptophysin, chromogranin A and p53 in immunohistochemistry. The patient currently underwent neoadjuvant chemotherapy with Etoposide and cisplatin for 4-cycles. We, with this, presented a rare case of SCNCB, along with a discussion on the clinical presentation, histological characteristics, management, and prognosis.